2013
DOI: 10.1080/14783363.2013.824714
|View full text |Cite
|
Sign up to set email alerts
|

Total quality management practices, competitive strategies and financial performance: the case of the Palestinian industrial SMEs

Abstract: The purpose of this paper is to examine the relationship between Total Quality Management (TQM) practices, competitive strategies -cost leadership and differentiation-and firm performance in the Palestinian economy. Within this study total quality management has been conceptualized as soft and hard practices, in congruence with the literature. An empirical analysis based upon an extensive validation process was applied to refine TQM, competitive strategies and financial performance scales. Data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 47 publications
3
77
1
Order By: Relevance
“…For instance, Palmer et al (2015) elucidated that firms analyze different markets based on their innovative strategy to gain CA because they believe that CA can significantly contribute firm's performance. Similarly, Herzallah et al (2014) and Ma (2000) resulted that CA has a significant positive association with firms' performance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Palmer et al (2015) elucidated that firms analyze different markets based on their innovative strategy to gain CA because they believe that CA can significantly contribute firm's performance. Similarly, Herzallah et al (2014) and Ma (2000) resulted that CA has a significant positive association with firms' performance.…”
Section: Discussionmentioning
confidence: 99%
“…While some scholars investigated only the internal reliability of the scale for each dimension and did not test its dimensionality (Sharma, 2006), others tested the construct's dimensionality using an EFA only (Calvo-Mora et al, 2013;Douglas & Judge, 2001;Lee & Lee, 2013;, or one type of CFA only (Barker & Emery, 2006;Delić et al, 2014;Herzallah et al, 2014;Kristal et al, 2010;Terziovski, 2006), or an EFA followed by one type of CFA (Ahire et al, 1996;Dow et al, 1999;Kaynak & Hartley, 2005;Kim et al, 2012). Although some studies found that QM is a multidimensional construct with a potentially unequal contribution of each dimension to achieving improved organisational performance, some researchers indicated that organisations must adopt an integrative approach to implementing QM because firms cannot capture full benefits when they implement only specific practices.…”
Section: Dimensionality Of Qm: Limitations Of Prior Studiesmentioning
confidence: 99%
“…QM has frequently been assumed to be a multidimensional construct measured by such dimensions as customer focus (CF) (Lee & Lee, 2013;Samson & Terziovski, 1999), top management commitment (Lakhal, 2009;Sharma, 2006), leadership (Calvo-Mora, Picón, Ruiz, & Cauzo, 2013;Sila & Ebrahimpour;, employee training (Banerji et al, 2005, Kim et al, 2012Su et al, 2008), employee relations (Flynn et al, 1995;Herzallah et al, 2014), quality information and reporting (Kim et al, 2012;Terziovski, 2006;Zu, Douglas, & Fredendall, 2008), benchmarking (Dow, Samson, & Ford, 1999;Powell, 1995), process management (PM) (Fening et al, 2008;Kim et al, 2012;Kristal et al, 2010), supplier management (SM) (Ahire & O'Shaughnessy, 1998;Kim et al, 2012;Tari, Molina, & Castejon, 2007), product design (Kaynak, 2003;Kim et al, 2012;Merino-Díaz, 2003), statistical process control (Ahire, Golhar, & Waller, 1996;Lau, Zhao, & Xiao, 2004), quality planning (Feng, Prajogo, Tan, & Sohal, 2006;Prajogo & Brown, 2004), and continuous improvement (Delić et al, 2014;Rahman & Bullock, 2005).…”
Section: Dimensionality Of Qm: Limitations Of Prior Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that TQM-adopting firms enjoy a competitive advantage over non-TQM (Powell 1995, Brah et al, 2000. Furthermore, numerous empirical studies, which attempt to examine the impact of TQM, support the proposition that a continuous commitment to TQM implementation has a significant positive effect on superior firm performance, as evidenced in the case of service firms (Agus, 2004), small and medium enterprises (Ahmad et al, 2014;Wali & Boujelbene, 2010;Salaheldin, 2009) and European companies (Boulter et al, 2013). Based on the preceding discussion, we propose the following hypothesis:…”
Section: Relationship Between Organizational Learning Tqm and Businmentioning
confidence: 99%